Crystallographic alignment of ZnO nanorod arrays on Zn2GeO4 nanocrystals : promising lattice-matched substrates - Yan, Chaoyi (2012)
We demonstrated that ternary Zn2GeO4 crystals could be used as potential lattice-matched substrates for ZnO nanorod array growth. Single-crystalline Zn2GeO4 nanowires were used as substrates for crystallographic alignment of ZnO nanorod arrays. Structural characterization verified the heteroepitaxial growth between the ZnO c-plane and Zn2GeO4 side facets, which was attributed to the small lattice mismatches. The semiconducting Zn2GeO4 crystals are of potential interest as novel alternative substrates for ZnO nanorod array growth.